Eloquence of Rhetoric in the Ancient Maghrebian Poetic Text "Poetry of Mohamed Eljazairy" - بوزيدي, سليم (Milev Journal of Research and Studies, 2019)
The present research paper aims at highlighting the elements of rhetorical formation in the poetic discourse of the Ancient Maghrebian poet Mohamed Eljazairy, where he incorporated the semantic level represented by metaphors, and the phonological level represented by the rhyme, the genus and the geometry of their voices in terms of features of expression and whispering.